Spontaneous rupture of choledochal cyst presenting in childhood - Kiresi, Demet Aydoğdu; Karabacakoğlu, Aydin; Dilsiz, Alaaddin; Karaköse, Serdar (The Turkish Journal of Pediatrics, 2005)
Spontaneous rupture of choledochal cysts is one of the rare complications, and can sometimes be the initial manifestation. It should be considered in the presence of bile-like fluid. A 10-year-old girl had acute onset of abdominal pain, vomiting, and elevated bilirubin, alkaline phosphatase, glutamic oxaloacetic transaminase and glutamic-pyruvic transaminase levels. There was no trauma in her history. In ultrasonography and computed tomography, dilated common bile duct, cystic mass of 10 x 6 cm, and free intraperitoneal fluid in abdominal cavity were demonstrated. Radiological methods, especially intraoperative cholangiography, should be performed for evaluation. We report a case of spontaneous rupture of the choledochal cyst with clinical and radiological findings.